(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The growth and development of children are influenced by whether proper nutrition is provided. Stunting is one type of nutritional disorder or malnutrition which is still a problem that occurs in our society. Educational activities are one way to help prevent stunting by providing adequate information to mothers about stunting and its prevention. A community service activity was carried out in Punggur Kecil Village by involving women and cadres through health education activities. This educational activity included the provision of materials on stunting, its prevention, and the treatment of stunting. The participants who are mothers attended to receive health education preceded by the spelling of the pre-test questions. After education, participants were also asked to answer post-test questions. There is a real difference between the results of the pre-test and post-test. This shows the importance of education given to mothers to increase understanding of stunting and its prevention. The role of health workers through the Puskesmas is urgently needed by involving cadres to assist health workers in identifying people who are at risk of having children with stunting so that stunting prevention and treatment can be taken from an early age.